Reflexões sobre o "Tratactus Logico-Philosophicus" - Pinheiro, Lilia Palmeira (2006)
To solve the problems of the language as representation is the focal point of the Tractatus. In order to accomplish this task, Wittgenstein propose a pictorial theory that seems to create a convincing strategy to assure that the logic rules of the world can determinate as the linguistic symbols, in their syntactic and semantic structures – not only the signs, when properly articulated into propositions, can effectively represent possible facts. Surprisingly, once that Wittgenstein solved this concern, he find out that the rules of language are the rules of the world, they share the same essence, and so, he ended to create not only a linguistic, but also an ontological theory as well. My primary intention is to consider the theory created by Wittgenstein, trying to rise up a few plausible problematic questions that appear in face of the perspective defended in the text.